2005
DOI: 10.1038/nn1391
|View full text |Cite
|
Sign up to set email alerts
|

Invariant computations in local cortical networks with balanced excitation and inhibition

Abstract: Cortical computations critically involve local neuronal circuits. The computations are often invariant across a cortical area yet are carried out by networks that can vary widely within an area according to its functional architecture. Here we demonstrate a mechanism by which orientation selectivity is computed invariantly in cat primary visual cortex across an orientation preference map that provides a wide diversity of local circuits. Visually evoked excitatory and inhibitory synaptic conductances are balanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
273
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 289 publications
(305 citation statements)
references
References 48 publications
29
273
1
Order By: Relevance
“…In all cells, the strong dynamic synaptic f luctuations provide the intrinsic ''noise'' to yield near contrast invariance. We examine the role of V1 architecture on orientation selectivity and show that, although extracellular selectivity for orientation is roughly independent of cortical location, intracellular measures are not, differing between neurons in iso-orientation regions and those near pinwheel centers, consistent with recent experiments (16). Finally, the role of synaptic f luctuations is elucidated in detail by studying the bifurcation structure of network activity in an idealized network model with statistically homogeneous coupling.…”
supporting
confidence: 73%
“…In all cells, the strong dynamic synaptic f luctuations provide the intrinsic ''noise'' to yield near contrast invariance. We examine the role of V1 architecture on orientation selectivity and show that, although extracellular selectivity for orientation is roughly independent of cortical location, intracellular measures are not, differing between neurons in iso-orientation regions and those near pinwheel centers, consistent with recent experiments (16). Finally, the role of synaptic f luctuations is elucidated in detail by studying the bifurcation structure of network activity in an idealized network model with statistically homogeneous coupling.…”
supporting
confidence: 73%
“…Indeed, coding efficiency depends on the shape of the neurons' tuning curves and on the structure of neuronal correlations. Importantly, despite the difference in local inputs to neurons in pinwheel centers and orientation domains, both these classes of cells have been described to have similar orientation tuning characteristics (9,34,35). In addition, optical imaging and electrophysiological studies have previously reported (36,37) that correlations between neurons depend only on the relative separation between cells and are independent on the cells' location on the cortical surface.…”
Section: Discussionmentioning
confidence: 99%
“…Since connections between cortical areas are excitatory, local recurrent inhibition would be needed to accomplish this. This, then, provides a simple explanation for the information benefit of recurrent networks that balance large excitatory inputs with local recurrent inhibition, a widely observed property of cortical circuits (Marino et al, 2005).…”
Section: Cortical Expansion Redundant Codes and Balanced Excitationmentioning
confidence: 94%